Pulp Treatment Need For Primary Teeth In Children Treated Under General Anesthesia - Valentina-Andreea Badea; Oana Slusanschi; Aneta Munteanu; Rodica Luca (Romanian Society of Oral Rehabilitation, 2013)
Aim of the study is to determine the pulp treatment need for primary teeth in children under general anaesthesia (GA) and to compare the different treatment patterns performed in special health care needs patients with the ones applied on healthy, uncooperative children. Material and methods Retrospective study on 57 patients treated under GA between 2011 and 2012 divided in two groups: disabled group (Group D) and healthy group (Group H). Caries experience indices for primary teeth (dmft/s) were calculated and treatment need was evaluated. Results The dmft/s indices values were similar between the two groups (NS, p >0.05). Regarding treatment methods used, a statistic significant value (p